2010
DOI: 10.1097/acm.0b013e3181cccbd4
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure Success: The Impact of Scholarly Concentrations on Students—A Literature Review

Abstract: The diversity of articles and variable results prevent definitive conclusions about the value of SCs. Findings suggest several implications for future SC program evaluations and educational research. The authors advocate increased rigor in evaluation designs to demonstrate SCs' true impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 45 publications
4
99
0
Order By: Relevance
“…3 The problem is widespread as even in residency, few programs provide a dedicated curriculum and possess the resources needed to support research, 2,4 despite the fact that such support provided to researchers advances the expansion of professional skills. [5][6][7][8] An environment supportive of research can lead to increased productivity. 6,9,10 Mentorship appears to be an especially critical form of support as it can enhance personal and professional development, 11 career satisfaction, 11 medical student career advancement, 12,13 and research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…3 The problem is widespread as even in residency, few programs provide a dedicated curriculum and possess the resources needed to support research, 2,4 despite the fact that such support provided to researchers advances the expansion of professional skills. [5][6][7][8] An environment supportive of research can lead to increased productivity. 6,9,10 Mentorship appears to be an especially critical form of support as it can enhance personal and professional development, 11 career satisfaction, 11 medical student career advancement, 12,13 and research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Capstone experiences take many forms, including research projects, internships, summer camps, interdisciplinary courses, arts-based performances, or comprehensive exams in lieu of a capstone. For the purpose of this paper, a research capstone program is defined as a required, structured curricular activity that immerses students into an in-depth scientific exploration of a specific area, beyond the conventional school curriculum 2,20,24,25 . Such a program implies employing the scientific method in a hands-on experience, which generates an academic product (e.g.…”
Section: Definitionsmentioning
confidence: 99%
“…The literature to date suggests that participation in school research may stimulate interest in pursuing research-related and academic careers 2,[32][33][34][35] , although data are not always easy to aggregate or compare due to the considerable variability between programs, student body, funding/stipend opportunities, areas of concentration, tracks or additional postgraduate degrees. It is interesting to note that in medical education earlier experiences with required student research revealed a low level of student support 36 , while more recent reports show that 80-94 % 2 consider that a research experience, if well conducted, should be a requirement for graduation.…”
Section: Criticalmentioning
confidence: 99%
See 2 more Smart Citations